2013
DOI: 10.1007/s00726-013-1462-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic aspects of the sulfate assimilation genes from Thalassiosira pseudonana

Abstract: Diatoms are unicellular algae responsible for approximately 20 % of global carbon fixation. Their evolution by secondary endocytobiosis resulted in a complex cellular structure and metabolism compared to algae with primary plastids. In the last years the interest on unicellular algae increased. On the one hand assessments suggest that diatom-mediated export production can influence climate change through uptake and sequestration of atmospheric CO2. On the other hand diatoms are in focus because they are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The redox insensitive ATP-S of Arabidopsis and that of Rhodophyta only contains 2 cysteines; 4 cysteines are present in Synechocystis PCC6803 and in most freshwater and marine cyanobacteria of genera different form Prochlorococcus and Synechococcus; in A. klebsii, five of the 6 cysteines in the ATP-S protein sequence are in different positions from those of the other eukaryotic algae (Giordano and Prioretti, 2014). The phylogeny of ATP-S was thoroughly described by Patron et al (2008): it is noteworthy that the genes encoding this enzymes in Arabidopsis have little sequence similarity with that of algae; the only exceptions are the sequences encoding the ATPS moieties of the fused ATP-S/APS kinase that are present in the genome of some haptophytes and heterokontophytes, which have a high degree of similarity with Arabidopsis ATP-S genes (Bromke et al, 2013;Giordano and Prioretti, 2014).…”
Section: Sulfurmentioning
confidence: 98%
“…The redox insensitive ATP-S of Arabidopsis and that of Rhodophyta only contains 2 cysteines; 4 cysteines are present in Synechocystis PCC6803 and in most freshwater and marine cyanobacteria of genera different form Prochlorococcus and Synechococcus; in A. klebsii, five of the 6 cysteines in the ATP-S protein sequence are in different positions from those of the other eukaryotic algae (Giordano and Prioretti, 2014). The phylogeny of ATP-S was thoroughly described by Patron et al (2008): it is noteworthy that the genes encoding this enzymes in Arabidopsis have little sequence similarity with that of algae; the only exceptions are the sequences encoding the ATPS moieties of the fused ATP-S/APS kinase that are present in the genome of some haptophytes and heterokontophytes, which have a high degree of similarity with Arabidopsis ATP-S genes (Bromke et al, 2013;Giordano and Prioretti, 2014).…”
Section: Sulfurmentioning
confidence: 98%
“…Although biochemical and kinetic data are not yet available for this enzyme, it has been hypothesized that the pyrophosphatase removes the PPi produced as a by-product of APS synthesis, thereby making the forward ATPS reaction irreversible. For what it is known, the only diatom that appears to constitute an exception to this pattern of isoform localization is Thalassiosira pseudonana : in this species, based on the presence/absence of a plastid transit peptide and sequence analysis, it was suggested that the isoform with the sole ATPS domain is located in the cytosol, whereas the APK-ATPS-pyrophosphatase isoform is in the chloroplast (Patron et al, 2008; Bromke et al, 2013). This localization is however to be taken with care, since the sequence was inferred from a raw contig at a time when few protein models were available for T. pseudonana genome (N. J. Patron, personal communication); even now, currently available softwares for the prediction of signal/transit peptides are not optimized for secondary endosymbiotic organisms and we were unable to unambiguously determine the nature of this transit peptide.…”
Section: Atps Isoformsmentioning
confidence: 99%
“…The same is true for the exchange of metabolites between plastids and the cytoplasm. There is still little knowledge on the sulfur uptake and assimilation (Bromke and Hesse 2013 ; Kopriva et al 2008 ). To shed more light on the biosynthesis of methionine in the model diatom T. pseudonana , we have performed a detailed phylogenetic analysis of each enzyme from the methionine biosynthesis pathway in this organism.…”
Section: Introductionmentioning
confidence: 99%